Optimization of Tax Policy as a State Regulation Mechanism of Formation and Distribution of Population Income - Asryan, Narine (YSU Journal of International Affairs, 2022)
In the conditions of modern socio-political realities, the issue of distribution and redistribution of income settlements will be accepted in full importance in connection with the processes of globalization and economic integration. At the same time, in many countries and regions the fight against inequality in the distribution and redistribution of income has reached significant progress, as the problem of poverty is still rising as a result of these tendencies. This article discusses the category of “income” as a source of livelihood for the population, as well as the basic directions of improvement of economic policy, in particular, the tax policy of the Republic of Armenia, the role of the latter in generating, distributing and redistributing the population income.